Agricultural chemical oxygen demand mitigation under various policies in China: A scenario analysis. (20th March 2020) - Tang, Kai; Hailu, Atakelty; Yang, Yuantao
Abstract: For many developing countries like China, agricultural production has been causing severe environmental issues, such as massive chemical oxygen demand (COD) emissions. However, limited studies have estimated regional total factor efficiency (TFE) and marginal abatement cost (MAC) of agricultural pollutants in developing countries. Multiple directional vectors have not been considered when using directional distance function approach to analyse agriculture production. In this study, we estimate TFE and MAC of COD emissions for the agricultural sector in China between 2006 and 2015. Three alternative scenarios, represented by three direction vectors, have been considered in a parametric directional approach. We find that there is no substantial efficiency improvement in China's agricultural production when all resource use and output production are considered. Averagely, eastern coastal provinces perform much better than western inland provinces. The average MAC estimate across all three scenarios is 11, 640 yuan/tonne. In addition, the MAC curves under three scenarios are generally characterised by increasing trends during 2006–2015. Abatement cost profiles are also characterised by substantial regional heterogeneity in MAC. Provinces in the East region have lower abatement costs than provinces in the West region. In general, our analysis suggests that there is space for China to achieve simultaneous improvements in agricultural production, pollution reduction, and resource saving, and agriculture is a potentially more cost-effective sector to reduce COD emissions compared to other sectors. Highlights: Agricultural COD mitigation under various policies in China are analysed. Three policy scenarios have been considered with a parametric directional approach. There is no substantial efficiency improvement in China's agricultural production. Eastern coastal provinces perform much better than western inland provinces. Agriculture is a potentially more cost-effective sector to reduce COD emissions.